2022
DOI: 10.1002/chem.202202453
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclic and Acyclicortho‐Aryloxy Diaryliodonium Salts for Chemoselective Functionalizations

Abstract: Two regioselective, high-yielding one-pot routes to oxygen-bridged cyclic diaryliodonium salts and ortho-aryloxysubstituted acyclic diaryliodonium salts are presented. Starting from easily available ortho-iodo diaryl ethers, complete selectivity in formation of either the cyclic or acyclic product could be achieved by varying the reaction conditions. The complimentary reactivities of these novel ortho-oxygenated iodonium salts were demonstrated through a series of chemoselective arylations under metal-catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…A selective nitration of unsymmetrical diaryliodonium salts has been reported. Here, electronic factors were more important, and nitration of electron‐deficient aryl moieties predominated [15a–b,f] . Other studies have noted a strong influence of the ortho ‐effect on the chemoselectivity of ortho ‐substituted iodonium salts, despite competing electronic preferences [15c–e] .…”
Section: Resultsmentioning
confidence: 89%
“…A selective nitration of unsymmetrical diaryliodonium salts has been reported. Here, electronic factors were more important, and nitration of electron‐deficient aryl moieties predominated [15a–b,f] . Other studies have noted a strong influence of the ortho ‐effect on the chemoselectivity of ortho ‐substituted iodonium salts, despite competing electronic preferences [15c–e] .…”
Section: Resultsmentioning
confidence: 89%
“…Further optimization revealed that the change from Et 3 N to inorganic bases was also not beneficial (entries 12 and 13). The addition of pyridine or its derivatives resulted in a drastically reduced yield (up to 11%; Table 1, entries [12][13][14][15][16][17]. We also varied the type of copper catalysts and found that both the change of the counter anion and the oxidation state led to a lower yield of 3a (entries 18-21).…”
Section: Resultsmentioning
confidence: 99%
“…12 However, the main application of diaryliodonium salts is still related to their ability to arylate a variety of nucleophiles (C, N, P, S, halogens, etc.). 1,2,[13][14][15][16][17][18] The use of diaryliodonium salts in the arylation of N-containing heterocyclic systems is particularly attractive, especially because of their ubiquitous application in drug development. Reactions with electron-rich heterocycles succeed under mild conditions without the addition of transition metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retained iodo substituent [15] is well suited for further derivatizations. [14,16] This strategy allows transformations of inexpensive and readily accessible cyclic amines into linear diarylamines with two structurally diverse N-aryl groups as well as various new polar functionalities at the carbon chain. Such complex products were inaccessible through our previous diarylation of primary amines (Scheme 1B) [14a] as formation of the required primary amine nucleophiles would require multistep synthesis, and reactions with unprotected polar-or oxidation sensitive functionalities on the amines often resulted in decomposition.…”
Section: Introductionmentioning
confidence: 99%